3D Meshlike Polyacrylamide Hydrogel as a Novel Binder System via in situ Polymerization for High‐Performance Si‐Based Electrode. Issue 2 (17th December 2019) - Woo, Hyungsub; Park, Kimin; Kim, Jaewon; Yun, Alan Jiwan; Nam, Seunghoon; Park, Byungwoo
Abstract: Silicon has been considered as a promising anode material due to its high theoretical capacity (3579 mAh g −1 ), however, it suffers from capacity degradation owing to the series of multiscale fractures in the electrode caused by the volume variation (≈300%) during phase transitions. The molecular/structural design of polymeric binders has been pivotal in overcoming the challenges to improve the integrity of Si anode via strong interactions between active materials and binders. In this respect, the covalently crosslinked polyacrylamide (PAM) network, which effectively maintains its mechanical strength and shape, is introduced as a novel binder system for Si active materials. Unlike the thermal crosslinking, the abundant polar‐functional groups, related to the strong interactions between Si and polymer, are not sacrificed in their network by virtue of the in situ polymerization. Through the PAM gel, the Si‐based electrode exhibits a superior capacity of ≈1526 mAh g −1 at an optimized crosslinker concentration after 500 cycles. In addition, the effect of the chemical/mechanical properties of PAM gel on the electrochemical properties of Si is adequately elucidated. The results will provide meaningful insight regarding the design of novel binders, especially in the application of the covalently crosslinked structure to Si‐based electrodes. Abstract : The 3D meshlike polyacrylamide gel is successfully applied as a binder for nano‐Si‐based electrode via in situ polymerization. The covalently crosslinked gel network with strong adhesion through hydrogen bonding guarantees superior electrochemical performance and improved integrity of the Si electrode.